A Tribute to the Father of Homoeopathy - Dr. Samuel Hahnemann (Homoeopathy for All, 2026)
The Samuel Hahnemann  Monument is a Neoclassical  memorial located at Scott Circle  NW in Washington, D.C..  Dedicated on June 21, 1900, it  honors the founder of homeopathy,  Samuel Hahnemann, and was  designed by sculptor Charles  Henry Niehaus and architect Julius  Harder. It features a seated bronze  statue on a granite exedra with  colorful Italian glass mosaic tiles.
Keywords: Cinchona plant; strong cathartics; totally disillusioned